Editorial - Wilhelm Heitmeyer; Douglas S. Massey; Steven F. Messner; James Sidanius; Michel Wieviorka (International Journal of Conflict and Violence, 2007)
The 2nd issue of the International Journal of Conflict and Violence focuses on the subject of terrorism. Terrorism has long been a worrisome phenomenon with serious impacts on and implications for the affected societies. Now, since 9/11, fighting international terrorism has moved to the very top of the agenda of the international community, or at least its western members. The special ICJV issue is intended to foster a deeper understanding of this critically important topic.